2001
DOI: 10.1159/000046134
|View full text |Cite
|
Sign up to set email alerts
|

Language Acquisition in Young German- Speaking Children with Cochlear Implants: Individual Differences and Implications for Conceptions of a ‘Sensitive Phase’

Abstract: The acquisition of language was studied longitudinally in a sample of 22 German-speaking children with cochlear implants (mean implantation age 29 months) and a control group of 22 normally hearing children. Spontaneous speech samples were collected over 27–36 months, starting at the the one-word stage. Results indicate that grammatical progress as measured by mean length of utterance was slower for cochlear-implanted children. However, there were substantial individual differences in the cochlear-implanted gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 13 publications
5
67
0
10
Order By: Relevance
“…As data from studies conducted by Szagun (2004) and TorresMonreal (2008, 2010) reveal, this domain of language acquisition is particularly important and sensitive to a lack of precise input provided by the cochlear implant. The capacity to develop morphosyntax easily in response to a well-specified input also tends to diminish with age, although the limits of a precise "sensitive period" cannot be fixed at the present time (Szagun, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As data from studies conducted by Szagun (2004) and TorresMonreal (2008, 2010) reveal, this domain of language acquisition is particularly important and sensitive to a lack of precise input provided by the cochlear implant. The capacity to develop morphosyntax easily in response to a well-specified input also tends to diminish with age, although the limits of a precise "sensitive period" cannot be fixed at the present time (Szagun, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Audition through the cochlear implant may not be sufficient to ensure optimum development of morphosyntactical abilities (Le Normand, 2003Spencer, 2004;Svirsky, Stallings, Lento, Ying, & Leonard, 2002;Szagun, 2001;. In a longitudinal study with German children, Szagun (2001) compared the increase of mean length of utterance (MLU) over a period of 18 months in two groups: deaf children with a cochlear implant and normally hearing peers initially matched for MLU = 1. She found that the cochlear implantees were delayed in the development of MLU, compared with the normally hearing children.…”
Section: Evidence That Cueing a Language Via Cued Speech Facilitates mentioning
confidence: 99%
“…This gap in reading achievement between children with hearing impairment and children with normal hearing sensitivity widens as severity of hearing loss increases (Karchmer, Milone, & Wolk, 1979). In recent and separate studies, use of cochlear implants (L. Spencer, Tomblin, & Gantz, 1998;Svirsky, Stallings, Lento, Ying, & Leonard, 2002;Szagun, 2001;Tomblin, Spencer, Flock, Tyler, & Ganz, 1999) and early exposure to sign language (Padden & Ramsey, 1998 have been positively associated with vocabulary and literacy skills. Further, multiple factors affect the reading skills of children with cochlear implants (Geers, 2002(Geers, ,2003Geers et al, 2002;Rayner, Foorman, Perfetti, Pesetsky, & Seidenberg, 2001), just as multiple factors affect the reading skills of children with normal hearing sensitivity (Geers, 2002;Geers et al, 2002;Rayner et al, 2001).…”
mentioning
confidence: 98%
“…However, children implanted at the youngest ages (12-23 months) tend to have more profound hearing losses than those implanted somewhat later (Nicholas & Geers, 2006b). Further, children with greater residual hearing preimplant have been found to exhibit better spoken language skills following cochlear implantation (Nicholas & Geers, 2006b;Szagun, 2001). This may be due to their early pre- …”
mentioning
confidence: 99%